Application of Behaviorally Anchor Rating Scale (BARS) Method to Assess Employee Performance at Diskoperindag Aceh Jaya - Asmaudi; Iing Pamungkas (LPPM Politeknik Aceh Selatan, 2023)
The application of performance has an important role and function for a company, of course, it will be related to the decisions that the office will take as an office strategy in the future. This also applies to the office of the Aceh Jaya Diskoperindag which is an aluminum injection company for spare parts for two-wheeled and four-wheeled vehicles. The current assessment that runs at the Aceh Jaya Diskoperindag office is an assessment based on criteria but currently the assessment of these criteria does not have standard standards so that employee assessments run subjectively, this causes problems for employees so that the current assessment is considered less effective and not in line with official goals. As a result, employees feel uncomfortable and unmotivated at work. To overcome these problems, a performance assessment is compiled based on the Behaviorally Anchor Rating Scale (BARS) method, this BARS method is expected to overcome problems in employee performance appraisal which was originally subjective to be more objective where in the end employees of the Aceh Jaya Diskoperindag office can work comfortably and have high motivation at work.